(untitled) (Journal of Applied Learning and Teaching, 2021)
At present, programming is a crucial competence for employability that is a requirement for engineering graduates. In India, all engineering students are required to register for an introductory programming course at the Freshmen level. Over the years, this introductory programming course is taught in a traditional chalk and talk approach. Traditionally, theory and lab classes were conducted separately. This kind of traditional approach limited students’ ability to think logically and develop problem-solving skills through programming. On that account, to encourage experiential learning which improves students’ logical thinking and problem-solving skills, this action research study looked at the possibility of implementing an integrated theory lab approach to a freshman C Programming course. Based on the course credits, the students met eight hours each week as part of the integrated implementation. A pretest posttest experimental research approach was used to examine the effects of the integrated pedagogical strategy. The classes for the students in the integrated approach were conducted directly in the laboratory to ensure meaningful learning and to enable more hands-on coding practice in the classroom simultaneously while the concepts were taught. Active and peer learning activities were designed to help students learn meaningfully. Due to the short intervention time and small sample size, there was no statistically significant effect to this integrated approach. However, the classroom activities increased hands-on practice time and regular formative assessments showed that students’ programming competency including logical thinking and problem-solving skills were improved through this integrated approach.